Broadcast Design in Cognitive Radio Ad Hoc Networks - Song, Yi (Springer eBooks, 2014)
This SpringerBrief investigates the special challenges of broadcast design in cognitive radio (CR) ad hoc networks. It introduces two broadcast protocols in CR ad hoc networks: a quality-of-service based broadcast protocol under blind information and a fully-distributed broadcast protocol with collision avoidance. A novel unified analytical model is also presented to analyze the performance of the broadcast protocols. This is the first book dedicated to the unique broadcast design challenges in CR ad hoc networks. The authors also discuss the recent research on the performance analysis of broadcast protocols. Broadcast Design In Cognitive Radio Ad Hoc Networks is designed for professionals and researchers working in the wireless networks industry. Advanced-level students in electrical engineering and computer science, especially those focused on wireless networks will find this information very valuable.